Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan pada PT. PLN Area Singkawang - Uray Suryadi (Universitas Muhammadiyah Pontianak, 2014)
The purpose of this study was to determine the effect on the performance of work discipline employees of PT. PLN Singkawang area. Methods using descriptive method with data collection consists of primary data include interviews, questionnaires, and observations and secondary data by studying the documentation. Saturated samples used in this study, so that the number of respondents is 144 people. The analysis is correlation and linear regression. The results of this study indicate that the correlation between the two is a weak correlation, based on the analysis of regression equation y = 3.284 to 0.004, which means if there is no increase in the value of labor discipline, then the value of the performance of employees is 3,284. Regression coefficient of -0.004 states that any decrease in the value of labor discipline the employee's performance is also decreased, by t test obtained t count equal to -1.176. From the above data obtained t = -1.176 while the results obtained for 1,656 ttabel (df = n-2 = 144-2 = 142). So the result that t < ttable or -1.176 <1.656 which means that the discipline of work does not affect significantly the performance of employees of PT. PLN Singkawang area and by coefficient of determination obtained a value of 0.10, meaning that the performance (Y) is influenced by 10% by the discipline of work, while the rest (100% -10% = 90%) is explained by other factors, and because of the small number of that means having a weak correlation between the two variables.